Purification and N‐terminal amino acid sequence of fructose‐6‐phosphate phosphoketolase from Bifidobacterium longum BB536 - Fandi, K.G.; Ghazali, H.M.; Yazid, A.M.; A.R., Raha (Oxford University Press, 2001)
Aims: The key enzyme in the fructose‐6‐phosphate shunt in bifidobacteria, Fructose‐6‐phosphate phosphoketolase (F6PPK; E.C. 4.1.2.22.), was purified to electrophoretic homogeneity for the first time from Bifidobacterium longum (BB536).